2005
DOI: 10.1002/pd.1187
|View full text |Cite
|
Sign up to set email alerts
|

Should determination of the karyotype be systematic for all malformations detected by obstetrical ultrasound?

Abstract: Each fetus with multiple malformations needs a chromosomal analysis. Within the group of isolated malformations, our study emphasizes that medical maternal history and the type of malformation need to be taken into account before performing a fetal karyotype.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
39
3
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 34 publications
(65 reference statements)
6
39
3
1
Order By: Relevance
“…In a review of prenatal detection of trisomy 21, 9.1% had some degree of hydronephrosis [127], and it was found to be more common in fetuses with trisomy 21 compared to normal controls (17% vs 5%) [128]. Staebler et al [129]. corroborated the increased incidence of serious abnormalities: significant chromosomal abnormalities were detected in 9% of fetuses with antenatal anomalies (including 3/22 of those with genito-urinary findings) and there was a 19% abnormality rate in fetuses with multiple anomalies (3/16 of these patients had a genitourinary abnormality).…”
Section: Role Of Antibiotic Prophylaxis In Children With Anhmentioning
confidence: 95%
See 1 more Smart Citation
“…In a review of prenatal detection of trisomy 21, 9.1% had some degree of hydronephrosis [127], and it was found to be more common in fetuses with trisomy 21 compared to normal controls (17% vs 5%) [128]. Staebler et al [129]. corroborated the increased incidence of serious abnormalities: significant chromosomal abnormalities were detected in 9% of fetuses with antenatal anomalies (including 3/22 of those with genito-urinary findings) and there was a 19% abnormality rate in fetuses with multiple anomalies (3/16 of these patients had a genitourinary abnormality).…”
Section: Role Of Antibiotic Prophylaxis In Children With Anhmentioning
confidence: 95%
“…corroborated the increased incidence of serious abnormalities: significant chromosomal abnormalities were detected in 9% of fetuses with antenatal anomalies (including 3/22 of those with genito-urinary findings) and there was a 19% abnormality rate in fetuses with multiple anomalies (3/16 of these patients had a genitourinary abnormality). Another review found karyotype abnormalities in 0.125% of patients with an isolated genital finding on US (sexual ambiguity) and 0.027% with an isolated finding of hydronephrosis [129,130]. ANH, in isolation, had the lowest correlation with karyotype abnormalities of all organ systems examined [129].…”
Section: Role Of Antibiotic Prophylaxis In Children With Anhmentioning
confidence: 96%
“…Gestational age was determined according to the earlier ultrasound. The main reasons for fetal karyotyping were categorized as described by Kessler et al 6 The patients were classified according to the number of major and minor sonographic markers observed before and after puncturing for fetal karyotyping in accordance with Raniga et al 7 Abnormalities identified through imaging studies performed during prenatal care were also classified as single or multiple defects, in accordance with Staebler et al, 8 before and after performing fetal karyotyping. To determine the congenital heart defect observed, we used the classification suggested by Botto et al 9 The Kaplan-Meier test was used to construct the survival curve, by means of the BioEstat 5.0 software.…”
Section: Objectivementioning
confidence: 99%
“…Although many authors have shown that fetuses with gastroschisis are usually reported with normal karyotype [8] , the resolution level of conventional cytogenetics techniques may underrepresent small structural abnormalities. The aim of this study was to investigate whether molecular investigation through CGH could improve the resolution of the cytogenetics reports and show abnormalities not seen through conventional techniques.…”
Section: Introductionmentioning
confidence: 99%